Role of Aluminum Doping in Anatase-to-Rutile Transformation from Thermodynamic View Point - Ho, Dai Q.; Kim, Seungchul (WILEY-V C H VERLAG GMBH, 2018)
Millions of tons of TiO-(2-) is being annually produced at the global scale utilizing AlCl-(3) as an additive for preferential formation of rutile phase. However, there is contrary data showing that Al doping is in fact working as an inhibitor for the anatase-rutile transformation (ART), raising questions on the role of Al-containing compound in the ART process. In this study, by using density functional theory (DFT) in combination with thermodynamic modeling, the role of Al-doping in bulk and surfaces of TiO-(2), and the co-effect of intrinsic defects on ART at plausible thermodynamic conditions of TiO-(2-) synthesis have been investigated(-). Our results show a conditional behavior, i.e., that Al dopant under reduction condition energetically promotes ART by stabilizing rutile bulk phase while it inhibits ART under oxidizing condition. On the surface, substitutional Al inverts surface energies of rutile and anatase phases, hence it promotes the direct formation of rutile from the beginning. This study will provide a better understanding on the role of the Al as a dopant, especially on the TiO2 surface, as this aspect is not well understood in spite of its wide application in the industry.
Keywords: PHASE-STABILITY; TIO2 PHOTOCATALYSTS; AB-INITIO; PHOTOEMISSION; TEMPERATURE; KINETICS